Development of methods and diagnostic kits for rapid microbiological monitoring of ballast water quality - Tay, Joo Hwa (2009)
The potential invasion of harmful microorganisms in Singaporees coastal waters from discharged ballast water can give rise to significant economic and ecological impacts as well as human-health consequences. Existing conventional monitoring methods are not appropriate for hallast water management because the analysis usually takes several days to complete and must be performed by an operator skilled in microbiology. The aim of the research project was to develop, to study and to optimize the methods and diagnostic kits suitable for rapid microbiological monitoring of ballast water quality by unskilled operator. The following methods have been developed and tested for microbiological monitoring of ballast water: (a) Hybridization of whole-cell rRNA of microorganisms with fluorescent-labelled oligonucleotide probes measured by flow cytometer; this is a fast 4 hour duration method performed by skilled technician in specialized laboratory; (b) The counting of the particles in narrow range of size, from 1 to 4 um, which is specific size of bacterial cells; this is a fast 0.5 hour duration method performed by unskilled operator in simple laboratory using flow cytometer or portable particle counter; (c) Chromogenie test of ballast water pollution by conforms indicating faecal pollution and risk of water-borne diseases from ballast water discharge; this is a simple 24 hour duration method performed by unskilled operator on board the ship or in the office.